O ensino de português brasileiro como língua adicional para fins acadêmicos : o gênero acadêmico resumo - Assumpção, Jéssica Skibinski (2022)
The increase in demand for international students made the Pontifical Catholic University of Rio Grande do Sul (PUCRS) seek to offer these students better study conditions and opportunities in their experience in Brazil and to improve their learning of Portuguese as an Additional Language (PAL). As a result, the idea for the Portuguese360 project emerged, an online course in Brazilian Portuguese designed by Antunes (2020), to which this dissertation continues. Based on the Speech Act theory in Pragmatics and the Hyland's Movements, this dissertation proposes the development of one of the course modules, the Abstract genre. We aim to analyze the informative abstracts of dissertations and theses from different areas of knowledge, as well as the most used representative and commissive verbs in each of them and their structures according to Hyland's Rhetorical Movements. For this, first, a pilot analysis of ten abstracts from the areas of Computing, Law and Linguistics collected from Lume digital collection of the Federal University of Rio Grande do Sul (UFRGS) was carried out to verify if the abstracts in Portuguese included the movements proposed by Hyland. For the second analysis, a questionnaire was developed and applied to the classes of foreign students at PUCRS, to find out more in depth what was their age group, graduation area, the level of proficiency in Portuguese Language, their objectives to be achieved when learning Portuguese, among other issues. From this questionnaire, we detected the three areas most frequented by these students, namely Accounting, Education and Medicine, and, from that, we collected ten abstracts from three different universities in each area so that we could analyze the specificities with which each area produces their academic abstracts. Thus, these two analyzes served as inspiration and guidance for the elaboration of activities that may, in the future, be part of the Portuguese360 course. Next, we proposed activities for the identification of Hyland’s moves and production of abstracts and we reflected on how Pragmatics studies can contribute, serving as a basis for the acquisition of PAL, since it takes into account not only the language skills of these students, but also their pragmatic skills, that is, their skills in how to make use of the language in different communication contexts, in the specific case of understanding and producing abstracts in PAL.